WBPS: A new web based tool for Personal Software Process - Thisuk S. (IEEE Computer Society, 2014)
Personal Software Process (PSP) is a structured framework which aims to improve overall performance of software engineers in an individual level. PSP practitioners need to extensively collect their development data using specially designed tools. However, all currently available tools have limitations such as disruption and unstructured documentation. These unfortunates could subsequently reduce potential performance of the practitioners. This paper proposes an alternative tool which systematically tackles other tools' limitation as well as offering several additional features. As a result, the engineers can focus their efforts more on the development and self-improvement. This paper also discusses a case study of an implementation of this new tool. © 2014 IEEE.